Pengaruh Pembayaran Digital Dan E-Commerce Terhadap Peningkatan Pendapatan Umkm Di Desa Celep Kabupaten Sidoarjo - Siti Nur Syarif'ah; Chairil Anwar; Achmad Wicaksono; Dian Fahriani (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This research aims to determine the influence of digital payments and e-commerce on the increase in income of MSMEs in Celep Village, Sidoarjo Regency.This type of research uses a quantitative method.The sample in this study consisted of 237 respondents, and the analysis was conducted using SPSS Version 27 software.The research results show that digital payments have a positive but not significant impact on revenue increase.E-commerce shows a positive impact on revenue growth.Then, the simultaneous results show that digital payments and e-commerce have an impact on increasing revenue.In this study, not many researchers have conducted research in rural areas because most researchers tend to focus on urban environments, thus not providing a comprehensive picture of the challenges and opportunities in rural areas.